PERAN GURU DALAM PEMBELAJARAN NUMERASI ANAK USIA DINI DENGAN MEDIA BALOK ANGKA - Siti Rohmah; Ia Hidarya; Rismawati; Tsaqifa Zulfa Aliema; Euis Nurlaela (Al Hanin, 2025)
Numeracy learning in early childhood serves as an essential foundation for developing logical thinking skills and understanding numerical concepts. However, many teachers still face challenges in selecting engaging and age-appropriate learning media. This study aims to describe the role of teachers in early childhood numeracy learning through the use of number block media. The research method employed a literature review by examining various scholarly sources related to numeracy learning strategies, the teacher’s role, and the effectiveness of concrete media in early childhood education. The results indicate that teachers play a crucial role as designers, implementers, and facilitators of enjoyable learning activities. Number block media help children understand numbers concretely through play-based activities. The study concludes that the use of number block media is effective in stimulating children’s numeracy skills. It is recommended that teachers continue to develop creativity in selecting contextual and engaging concrete media for early childhood learners.